2010
DOI: 10.1016/j.virol.2010.06.038
|View full text |Cite
|
Sign up to set email alerts
|

HBV mutations in untreated HIV-HBV co-infection using genomic length sequencing

Abstract: HIV infection has a significant impact on the natural progression of hepatitis B virus (HBV) related liver disease. In HIV-HBV co-infected patients, little is known about mutations in the HBV genome, which can influence severity of liver disease. The aim of this study was to characterize and to determine the frequency of known clinically-significant mutations in the HBV genomes from HIV-HBV co-infected patients and from HBV mono-infected patients. To accomplish this, genomic length HBV sequencing was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 61 publications
5
31
1
Order By: Relevance
“…Even so, the frequency of mutations under positive selection was lower among patients co-infected with HBV and HIV. This is consistent with the weaker HBVspecific T-cell response observed in HIV-HBV coinfection [Audsley et al, 2010].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Even so, the frequency of mutations under positive selection was lower among patients co-infected with HBV and HIV. This is consistent with the weaker HBVspecific T-cell response observed in HIV-HBV coinfection [Audsley et al, 2010].…”
Section: Discussionsupporting
confidence: 87%
“…Two different factors, such as the high HBV replication capacity and the lack of proofreading activity by the HBV polymerase, contribute to the development of quasispecies complexity and diversity during infection. The HBV quasispecies composition appears to be different when HIV is present, as previously reported [Cassino et al, 2009;Audsley et al, 2010]. The present study demonstrates that the intra-host analyses of HBV isolates revealed high complexity and diversity among patients infected with HBV exhibiting higher numbers of viral variants and genetic distance.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…43 The presence of deletion mutants in HBV from HBV/HIV co-infected individuals has been described in genotype A, both subgenotype A1 44 and subgenotype A2. 45 PreS2F22L was found in four isolates from HBsAg-positive HBV/HIV co-infected individuals and was found to be significantly associated with G1896A. PreS2F22L has been significantly associated with cirrhosis 46 and has been shown to be a risk factor for the development of HCC in Chinese patients infected with genotype C 47 and in Indian patients infected with genotype D. 46,48 HIV infection has been intimated to increase the hepatocarcinogenic potential of HBV.…”
Section: Discussionmentioning
confidence: 97%
“…This mutation results in premature termination of the deduced HBV precore and core genes and was associated with high HBV viral load. PreS2 deletions were observed more frequently in co-infection (Audsley et al, 2010). …”
Section: Hiv Co-infectionmentioning
confidence: 97%